Plasma deposition of hydrophobic coatings on structured surfaces for condensation and heat transfer applications - Gloess, D.; Frach, P.; Maicu, M.; Holst, E.; Schmittgens, R.; Gerlach, G.; Lu, C.H.; Roch, T.; Bieda, M.; Lasagni, A.; Beckmann, M. (International Conference on Plasma Surface Engineering, 2013)
The control of vapor condensation processes by suitably prepared surfaces is a prominent research area with important applications in the industry. For example, it is well known that the efficiency of condensation heat exchangers can be significantly increased when the vapor condenses to form droplets on the surface, instead of a closed film which does not wet the surface. In the present work, hydrophobic thin films are deposited via plasma CVD processes on metallic surfaces to investigate the condensation of water vapor on these surfaces. The drop-wise condensation on the coated surfaces is analyzed by optical microscopy and the effect on the heat transfer is measured by heat flux measurements. In order to show the potential of the deposition process for industrial applications and to investigate the effect of drop-wise condensation on heat transfer, copper (Cu) substrates were coated with a plasma polymer film using an organosilicon monomer (Hexamethyldisiloxane, HMDSO) as a precursor. In addition, the effect of surface roughness on the drop-wise condensation is presented because the static contact angle of water on hydrophobic surfaces depends strongly on surface topography.